2016
DOI: 10.3389/fmicb.2016.01794
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Nitrogen Metabolite Repression Regulator Gene nmrA in Aspergillus flavus

Abstract: In Aspergillus nidulans, the nitrogen metabolite repression (NMR) regulator NmrA plays a major role in regulating the activity of the GATA transcription factor AreA during nitrogen metabolism. However, the function of nmrA in A. flavus has not been previously studied. Here, we report the identification and functional analysis of nmrA in A. flavus. Our work showed that the amino acid sequences of NmrA are highly conserved among Aspergillus species and that A. flavus NmrA protein contains a canonical Rossmann fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 51 publications
2
55
0
Order By: Relevance
“…The growth and mycotoxin production in fungi is also influenced by the available carbon and nitrogen sources and the corresponding regulators [ 20 , 39 , 40 ]. The transcription factors CreA, AreA and NmrA play important roles in modulating the expression of genes for utilizing these nutrient sources [ 14 , 16 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and mycotoxin production in fungi is also influenced by the available carbon and nitrogen sources and the corresponding regulators [ 20 , 39 , 40 ]. The transcription factors CreA, AreA and NmrA play important roles in modulating the expression of genes for utilizing these nutrient sources [ 14 , 16 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the nitrogen metabolic regulation, although there was no obvious significant difference in AreA expression, NmrA demonstrated lower levels of transcription in A. alternata with magnolol treatment. NmrA appears to affect gene expression through physical interaction with AreA [ 42 ], and also be involved in the mycotoxin biosynthesis and virulence of pathogens [ 18 , 40 ]. The NmrA deletion partially restricted the production of aflatoxin [ 40 ] and deoxynivalenol [ 43 ] in some minimal media with one amino acid as the sole nitrogen resource.…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin B1 (AFB1) of all the mycotoxin holds the highest toxicity. It is widely distributed across agricultural products and acts as a potent carcinogen, mutagen and teratogen (Yang et al, 2015;Han et al, 2016;Xing et al, 2016). The protracted consumption of AFs in both humans and animals leads to immunosuppression, growth impairment and DNA damage (Khlangwiset et al, 2011;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that the NT mutant was a defect in aflatoxins biosynthesis. Former studies have demonstrated that specific nutrients, like vitamins, amino acids and fatty acids are necessary for AFs formation [30]. In the AF biosynthesis pathway, it starts from acetyl-CoA, which is synthesized via oxidative decarboxylation of pyruvate, β-oxidation of fatty acids, or from ketogenic amino acids in primary metabolism [31].…”
Section: Discussionmentioning
confidence: 99%